How to do a combined endoscopic and tailored open extraperitoneal approach for large congenital inguinoscrotal hernia. Issue 7 (13th May 2021) - Diab, Jason; Badiani, Sarit; Berney, Christophe R.
Abstract : Large inguinoscrotal hernias require experienced and skilful laparoscopic hernia surgeons to reap the benefits of laparoscopic versus open surgery. We advocate for an alternative hybrid TEP‐open technique that allows tissue extraction away from the groin area, whenever necessary, thus avoiding more painful conventional open herniorrhaphy incision.